2018
DOI: 10.1038/s41598-018-33550-4
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of porcine IVM medium supplementation with follicular fluid become reflected in embryo quality, yield and gene expression patterns

Abstract: Oocyte and embryo developmental competence are shaped by multiple extrinsic and intrinsic factors. One of the most extensive research areas in the last decade is the regulation of lipid metabolism in oocytes and embryos of different species. We hypothesized that differences in developmental competence of oocytes and embryos between prepubertal and cyclic gilts may arise due to distinct fatty acid profiles in follicular fluid. We found that supplementation of oocyte maturation media with follicular fluid from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…These results confirmed that the sexual maturity of the donor had a significant influence on oocyte competence and availability, validating the model used in this study. The supplementation of IVM medium with follicular fluid influences the quality of the oocyte obtained from prepubertal females (Pawlak et al, ). In this study, despite the supplementation of IVM medium with follicular fluid from cycling sows, we observed differences in the dynamics of gene expression, the lipid profiles and DNA methylation reprogramming in oocytes from prepubertal gilts compared to those from cycling sows.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that the sexual maturity of the donor had a significant influence on oocyte competence and availability, validating the model used in this study. The supplementation of IVM medium with follicular fluid influences the quality of the oocyte obtained from prepubertal females (Pawlak et al, ). In this study, despite the supplementation of IVM medium with follicular fluid from cycling sows, we observed differences in the dynamics of gene expression, the lipid profiles and DNA methylation reprogramming in oocytes from prepubertal gilts compared to those from cycling sows.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, changes of lipid droplets number during oocyte maturation depends on e.g. the reproductive status of the female, which has been confirmed in cattle [38] and pigs [40]. In bovine oocytes of prepubertal heifers there is observed lower number of lipid droplets when compared to mature cows [38].…”
Section: Fatty Acid Metabolism Within the Follicular Environmentmentioning
confidence: 75%
“…In bovine oocytes of prepubertal heifers there is observed lower number of lipid droplets when compared to mature cows [38]. In contrary, significantly lower number of lipid droplets is present in oocytes originating from cyclic pigs when compared to prepubertal [40]. The observed differences are difficult to explain, since these two species show different requirements for the lipid metabolism.…”
Section: Fatty Acid Metabolism Within the Follicular Environmentmentioning
confidence: 92%
“…Therefore, FF compounds such as amino acids, fatty acids, hormones and growth factors may affect both the oocyte and the cumulus cells during the entire period of in vitro maturation, making the system suboptimal. The issue of data reproducibility arises due to the stimulatory or the inhibitory effect of FF on oocytes and embryos, depending on its quantitative and qualitative composition (Bagg et al, 2007Grupen et al, 2010, Pawlak et al, 2018. Moreover, working with an in vivo collected FF, demonstrating the action of a single factor is more difficult than in cattle, where IVM medium is supplemented with defined components such as fatty acids or amino acids.…”
Section: Pig -Early Embryonic Developmentmentioning
confidence: 99%